Naringenin prevents NAFLD in the diet-induced C57BL/6J obesity model by regulating the intestinal barrier function and microbiota - Ruyang Yu; Yinping Gu; Lanyan Zheng; Zhongjie Liu; Yifei Bian (Journal of Functional Foods, 2023)
Objectives: The intestinal immunity and the microbiota play an essential role in metabolic syndrome associated with obesity, for instance, non-alcoholic fatty liver disease (NAFLD). However, the effects of naringenin on diet-induced NAFLD and intestinal functions have not been reported. Methods: The effects of naringenin on NAFLD were assessed in C57BL/6J administrated with a high-fat diet (HFD) and high-fat diet with 0.1% naringenin (HFN). The ELISA, histopathology, and flow cytometry were conducted to assess the effects of naringenin on the liver and intestinal inflammation. The FITC-dextran, western blot, and real-time quantitative PCR were used to evaluate the effects of naringenin on intestinal permeability. The regulatory effects of naringenin on intestinal microbiota in NAFLD mice were detected by 16S rRNA sequencing. Results: Naringenin could curb weight gain in obese mice, reduce the content of triglyceride (TG) and total cholesterol (TC) in blood and liver, and even improve the steatosis of liver cells. Naringenin alleviated the rate of infiltration in dendritic cells and macrophages in colon tissues and inhibited inflammatory factors in the intestinal and liver tissues. Naringenin reduced the gut barrier permeability caused by HFD and increased the expression of tight junction proteins (TJs). Furthermore, naringenin significantly improved the cecal microbiota disorder by enhancing the growth of salutary symbiotic bacteria and restraining the colonization of pathogenic bacteria. Conclusion: Naringenin could relieve metabolic disorders caused by HFD and improve gut barrier functions, thereby inhibiting the migration of intestinal microorganisms and products via the gut-liver axis, thus preventing NAFLD.